Relationship of CSR, innovation, human resource practices, and competitive advantage: a test of two mediation models - Almohtaseb, Ahmad; Alabaddi, Zaid; Gangoor, Vijaya (Business: Theory and Practice, 2025)
In the dynamic business environment, manufacturing companies need a competitive advantage for long-term survival, and this can be achieved by focusing on CSR, HR practices, and innovation. While CSR is often viewed as a tool for enhancing corporate reputation and addressing societal concerns, its potential to drive innovation and contribute to a sustainable competitive advantage remains underexplored. Additionally, the role of human resource practices in mediating these relationships is not well understood. This research seeks to address the gap in the literature by examining the relationships between CSR, innovation, human resource practices, and competitive advantage, and investigating how these elements interact to help organizations gain a competitive edge in a rapidly evolving market environment. The current research aims to highlight the influence of CSR on competitive advantage. Moreover, it also examined how mediation mechanisms of innovation and HR practices influence the effect of CSR on competitive advantage. The current study utilized quantitative research approach and the data were gathered from the managers of manufacturing companies in Jordan. The results highlighted that CSR significantly influences innovation, HR practices, and competitive advantage. Furthermore, innovation and HR practices both significantly mediate the relationship between CSR and competitive advantage. The findings of this study can act as a guideline for managers of Jordanian manufacturing companies aiming to achieve competitive advantage.